2020
DOI: 10.1039/d0ra07254k
|View full text |Cite
|
Sign up to set email alerts
|

Strong electron acceptor additive based spiro-OMeTAD for high-performance and hysteresis-less planar perovskite solar cells

Abstract: A perovskite solar cell with DDQ doped spiro-OMeTAD HTL delivers a champion power conversion efficiency of 21.16%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The absorption spectra of all three HTM thin films are displayed in Figures 4 a and S5 . The pristine Spiro-OMeTAD exhibits strong absorption in the UV region, with a peak maximum at 374 nm, which is consistent with data published previously by Wang et al 36 In contrast, the absorbance of pristine EDOT-Amide-TPA and TPABT films were very low in the UV region. 37 We found this new material, TPABT, to be more transparent in the visible region compared to both Spiro-OMeTAD and EDOT-Amide-TPA ( Figure S6 ), which will allow more photons to be absorbed by the perovskite layer and improve the PCE.…”
Section: Resultssupporting
confidence: 91%
“…The absorption spectra of all three HTM thin films are displayed in Figures 4 a and S5 . The pristine Spiro-OMeTAD exhibits strong absorption in the UV region, with a peak maximum at 374 nm, which is consistent with data published previously by Wang et al 36 In contrast, the absorbance of pristine EDOT-Amide-TPA and TPABT films were very low in the UV region. 37 We found this new material, TPABT, to be more transparent in the visible region compared to both Spiro-OMeTAD and EDOT-Amide-TPA ( Figure S6 ), which will allow more photons to be absorbed by the perovskite layer and improve the PCE.…”
Section: Resultssupporting
confidence: 91%
“…EIS was further conducted to evaluate the interface resistance (R ct ) of the devices. 56 The semicircle in the high frequency implied the interfacial charge transfer. 57 As shown in Figure 6c, the recombination resistance of the CHEApassivated device is significantly lower than that of the pristine device, which indicated that the CHEA passivation suppressed charge recombination and enhanced effective charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…EIS was further conducted to evaluate the interface resistance ( R ct ) of the devices . The semicircle in the high frequency implied the interfacial charge transfer .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Spiro‐OMeTAD is widely used as an organic HTL in PSCs. However, such HTL in pristine form suffers from low hole mobility and conductivity, which requires various dopants, such as t‐BP and hygroscopic LiTFSI salt, to work as an efficient HTL [16] . Concurrently, the inclusion of such dopants increases the overall HTL's cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, such HTL in pristine form suffers from low hole mobility and conductivity, which requires various dopants, such as t-BP and hygroscopic LiTFSI salt, to work as an efficient HTL. [16] Concurrently, the inclusion of such dopants increases the overall HTL's cost. Additionally, the widely used HTL (SpiroOMeTAD) involves a complicated synthesis procedure.…”
Section: Introductionmentioning
confidence: 99%